A new method for non-invasive estimation of human muscle fibre type composition in athletics - Baguet, A.; Bex, T.; Derave, W. (New Studies in Athletics, 2014)
ABSTRACT The composition of an individual's muscles is a talent predictor in athletics. However, the invasive technique of muscle biopsy, the accepted means for determining muscle fibre population, is unsuitable for talent identification. Non-invasive possibilities tested to date are also unsatisfactory. Recently, proton magnetic resonance spectroscopy (1H-MRS) has been used to measure muscle metabolites including carnosine, which is present in different concentrations in type-1 (slow twitch) and type-II (fast twitch) fibres. The authors aimed to determine if this means is suitable for estimating muscle fibre composition. Carnosine levels measured by 1H-MRS in the gastrocnemius muscles of athletes and control subjects and then compared to untrained subjects who underwent both 1H-MRS and muscle biopsies significantly correlated to the area occupied by type II fibres in explosive event athletes, with endurance athletes registering lower levels compared to the reference population. Similar trends were found in both young and ex-athletes. The authors conclude that the method is valuable for estimating muscle fibre composition but point out its limitations, including cost. This article has been adapted from a manuscript previously published by the Public Library of Science.